Economic growth devoid of social progress: the situation in Brussels - Gilles Van Hamme; Isaline Wertz; Valérie Biot (Brussels Studies)
This article examines the economic and social evolutions in Brussels over the past two decades. Despite favourable economic evolutions during this period, the social situation has continued to deteriorate, with increasingly higher unemployment rates and growing social inequalities. Although this situation exists in the other major Belgian cities, it is much more pronounced in Brussels. This is due to multiple dynamics, including the evolution of the labour demand towards increassingly higher requirements in terms of skills, which plays an important role by excluding the least qualified people from the labour market. The aggravating role of the spatial concentration of disadvantaged populations – which is especially pronounced in Brussels – is also emphasised. The article ends with a discussion of the pertinence of regional policies, in particular as regards the emphasis placed on the international positioning of Brussels.